Ustadz Ridho Febri’s Rhetoric On The Podcast ‘Responding to Tests and Problems’ on Sonny Aby Kim’s Youtube Channel From the Perspective of Aristotle’s Rhetoric - Fauzul Azmi Daulay; Khatibah Khatibah; Hilda Syahrani (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
The development of digital media has made podcasts an increasingly popular medium for delivering Islamic preaching messages because they are communicative and easily accessible. However, studies examining Islamic preaching rhetoric based on Aristotle’s rhetorical theory in podcast media remain limited. This study aims to analyze the use of Aristotle’s three rhetorical elements ethos, pathos, and logos by Ustadz Ridho Febri in the podcast “Menyikapi Ujian dan Masalah” on Sonny Aby Kim’s YouTube channel. This study employed a qualitative Grounded Theory approach. Data were collected through observation and documentation of the podcast content and analyzed using Strauss and Corbin’s coding procedures, namely open coding, axial coding, and selective coding. The findings reveal that ethos is reflected in the speaker’s credibility and experience in conveying Islamic messages, pathos is demonstrated through his ability to build empathy and emotional connection with the audience, and logos is shown in the logical and systematic presentation of arguments related to life’s challenges. The integration of these three rhetorical elements creates persuasive and effective Islamic preaching that strengthens audience engagement and understanding. The novelty of this study lies in highlighting the integrated use of ethos, pathos, and logos in podcast-based Islamic preaching within contemporary digital media.